Data for project "Cellulose nitrate lacquer on silver objects", RAÄ-2021-3131 - Canosa, Elyse; Bylund Melin, Charlotta (Swedish National Heritage Board, 2024)
Data from the project "Cellulose nitrate lacquer on silver objects" (RAÄ-2021-3131). Each zip file contains an Instrument report file which gives sample names and descriptions, instrument parameters, spectra figures and in some report interpretation notes. Data from the following analytical techniques is included: 1. Scanning electron microscopy with energy dispersive x-ray spectroscopy (SEM-EDS); 2. Polarized light microscopy (PLM); 3. Fourier transform infrared spectroscopy (FTIR).

Data was collected as a continuation of (but after the publication of) the bachelor theses "A greener solution: Investigating the potential use of Green Solvents to remove cellulose nitrate lacquer from silver objects" by Evelina Borén (https://hdl.handle.net/2077/72648) and "The use of gels for the removal of cellulose nitrate lacquer on silver" by Katayon Miri (https://hdl.handle.net/2077/72650), both at the Department for Conservation, University of Gothenburg. The project is also part of a larger invesitgation about removing cellulose nitrate lacquer on silver objects, supported by European Union funded IPERION HS project (2020-INFRAIA-2019-1).

Instrument reports including technical specifications of each instrument can also be found under DOI 10.5281/zenodo.10869595 .
Keywords: Microscopy; Electron microscopy; Nationalmuseum; Cellulose nitrate; Heritage conservation; Gels; Lacquer; green solvents; silver; FTIR; RAÄ-2021-3131; History and Archaeology; Historia och arkeologi